Biographie et psychanalyse des femmes surréalistes - Georgiana Colvile (Itinéraires)
This essay explores the relevance of biography and psychoanalysis as hermeneutic approaches to the literary and plastic production of women surrealists. Women were usually marginalized within the movement(s), and used their creativity to achieve an autonomous identity. The result was a proliferation of self expression, mainly autobiographies and self-portraits. Their lives, desires and traumas mirror their art, so biography and psychoanalysis provide a necessary point of departure for other theoretical investigations. Colvile concentrates on texts by Claude Cahun and Leonora Carrington.